Kekuatan Hukum Putusan Dewan Kehormatan Penyelenggara Pemilu terhadap Penetapan Calon Presiden dan Wakil Presiden - Dananjaya, Adhitya Arum; Hadi, Syofyan (CV. Era Digital Nusantara, 2025)
This research discusses the legal strength of the decision of the Election Organizer Honorary Council (DKPP) regarding the determination of presidential and vice presidential candidates by the General Election Commission (KPU). DKPP is an institution tasked with enforcing the code of ethics for election organizers by issuing final and binding decisions. However, this